The role of body image in treatment decision-making and post-treatment regret following prostatectomy. (8th October 2020) - Shiridzinomwa, Constance; Harding, Sam
Abstract : Three main treatments are offered to men with localised prostate cancer: active monitoring, radiotherapy and prostatectomy. The aim of this research was to explore the role of body image in treatment decision-making and post-treatment regret following prostatectomy for localised prostate cancer. Data were collected via nine semi-structured interviews. Interviews underwent thematic analysis and four themes emerged: need to prolong life, loss of function and self, post-surgery effects on body image and confidence, and coping strategies. Participants revealed that loss of erectile function following surgery resulted in reduced self-confidence, and changes in their perception of their body.